Review of the practical manual for physicians «Mediastinitis» by M. M. Abakumov (Moscow, MK, 2020: 296. (In Russ.)) - I. M. Samokhvalov (Вестник хирургии имени И.И. Грекова)
A review of the manual for physicians «Mediastinitis» published in 2020, written by the famous Russian surgeon and scientist Professor Mikhail Mikhailovich Abakumov, is presented. The manual is based on the study of pathogenesis and practical experience in the diagnosis and treatment of patients with various forms of mediastinitis at the Sklifosovsky Research Institute for Emergency Medicine for 40 years. Sections of the manual include the history of the problem, terminology and classification issues, pathogenesis, clinical presentation and diagnosis, surgery and postoperative treatment of mediastinitis. The manual is intended for a wide range of surgeons who may be involved in acute mediastinitis diagnosis and treatment.